PENERAPAN DIGITAL MARKETING TERHADAP UMKM SEBAGAI PEMASARAN DALAM MENGHADAPI REVOLUSI - Felicia; Kelly, Angel; Hartati, Ery; Ariansyah, Nova; Djunaidi, Sherdian (Politeknik Negeri Sriwijaya, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the economy and have great potential for significant growth. However, even though the digital era has penetrated various sectors, there are still many MSMEs that have not taken advantage of the marketing opportunities offered by digital marketing. Data from Kompas.id in 2022 reveals that around 65 million MSMEs have not adopted digital marketing strategies, which is largely due to a lack of technological understanding among business actors. Therefore, this Community Service Activity aims to provide direct training and guidance to MSMEs, such as Lin's Culinary, in utilizing social media such as Instagram and the graphic design tool Canva. It is hoped that through this activity, MSME owners can increase their understanding and skills in utilizing digital platforms for marketing purposes, and can increase the competitiveness and sustainability of their businesses. Keywords: Canva, Digital Marketing, Instagram, MSMEs